Enzyme potentiated desensitisation in treatment of seasonal allergic rhinitis: double blind randomised controlled study. Issue 7409 (31st July 2003) - Radcliffe, Michael J; Lewith, George T; Turner, Richard G; Prescott, Philip; Church, Martin K; Holgate, Stephen T
Abstract : Objective To assess the efficacy of enzyme potentiated desensitisation in the treatment of severe summer hay fever poorly controlled by pharmacotherapy. Design Double blind randomised placebo controlled parallel group study. Setting Hospital in Hampshire. Participants 183 participants aged between 18 and 64 with a history of severe summer hay fever for at least two years; all were skin prick test positive to timothy grass pollen. 90 randomised to active treatment; 93 randomised to placebo. Interventions Active treatment: two injections of enzyme potentiated desensitisation, given between eight and 11 weeks apart, each comprising 200 Fishman units of β glucuronidase, 50 pg 1, 3-cyclohexanediol, 50 ng protamine sulphate, and a mixed inhaled allergen extract (pollen mixes for trees, grasses, and weeds; allergenic fungal spores; cat and dog danders; dust and storage mites) in a total volume of 0.05 ml of buffered saline. Placebo: two injections of 0.05 ml buffered saline solution. Main outcome measures Proportion of problem-free days; global rhinoconjunctivitis quality of life scores assessed weekly during pollen season. Results The active treatment group and the placebo group did not differ in the proportion of problem-free days, quality of life scores, symptom severity scores, change in quantitative skin prick provocation threshold, or change in conjunctival provocation threshold. No clinically significant adverse reactions occurred. Conclusions Enzyme potentiated desensitisation showed no treatment effect in this study.